Evaluation of the Association Between Matrix Metalloproteinase 11 and Intervertebral Disc Disease - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2015)
AIM: The intervertebral disc starts to degenerate when a human being begins to stand and learn to walk. It is known that many extrinsic, intrinsic and genetic factors play a role in disc degeneration. In this study, we examined whether the matrix metalloproteinase 11 might be associated with intervertebral disc degeneration. MATERIAL and METHODS: Fifty-six patients with lumbar disc herniations who were operated at Gortepe Education and Research Hospital, Neurosurgery Clinic between September 2008 and December 2009 were prospectively reviewed. History and complaints were obtained from the case reports. Neuroradiological evaluation was performed with magnetic resonance imaging. Surgical findings of cases were reported in the operation notes. Microscopic posterior hemipartial laminectomy and discectomy were performed in all cases. Degenerated herniated disc material of all cases extracted during surgery was evaluated with immunohistochemical staining in Marmara University, Institute of Neurological Sciences, Pathology Laboratory. RESULTS: Comparing the immunohistochemical staining of cases who were 50 years or younger and cases who were over 50 years old, statistical significance was determined. CONCLUSION: Matrix metalloproteinase 11 has a role in degenerating intervertebral disc disease, but it is not the only factor. Matrix metalloproteinase 11 might be a genetic factor in young-middle aged patients.
Keywords: Intervertebral disc degeneration; Intervertebral disc displacement; Matrix metalloproteinase 11; Middle age; DEGENERATION; CELLS; EXPRESSION; GROWTH; VOLVO; RISK